Incidence of subchorionic hematoma and contributing factors in assisted reproductive technologies—a retrospective cohort study - Wei, Wei; Qiu, Xue Chang; Tang, Ni; Liang, Zhuo; Wu, Jinxiang; Huang, Pinxiu (Frontiers in Medicine, 2025)
BackgroundTo explore the incidence of subchorionic hematoma (SCH) in IVF-ET (In vitro fertilization-embryo transfer, IVF-ET) fresh, IVF-FET (In vitro fertilization-freeze–thaw embryo transfer, IVF-FET), PGT-FET (preimplantation genetic testing-freeze–thaw embryo transfer, PGT-FET), AIH (artificial insemination by husband, AIH), and natural pregnancy (NP), and to analyze contributing factors.MethodsThis is a retrospective cohort study. Patients were included: IVF-fresh ET, IVF-FET, PGT-FET, AIH, and NP patient groups. The incidence of SCH in different ART and effect of SCH on pregnancy outcome were compared, Further, multivariate analyses of the occurrence of SCH were conducted.ResultsThe incidence of SCH with IVF-fresh ET, IVF-FET, PGT-FET, AIH and NP was 27.50%, 22.56%, 16.86%, 12.95%, and 13.02%, respectively. Compared with the incidences of SCH with AIH and NP that for IVF-fresh ET and IVF-FET transfer were significantly increased (p < 0.05). The occurrence of SCH was not significantly associated with miscarriage and was significantly negatively correlated (p < 0.05) with high-quality embryos.ConclusionThe incidence of SCH in ET was increased compared with that in the Not ET groups, especially after fresh ET. ET unavoidably seems to contribute to the development of SCH; however, it does not affect the pregnancy outcome.